(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Protein and carbohydrate content in macroalgae are required to optimize the utilization of macroalgae from Sepanjang Beach. This study aims to determine the protein and carbohydrate content of macroalgae at Sepanjang Beach, Yogyakarta. This research was conducted in August-September 2020. The research materials included macroalgae of Ulva lactuta, Palmaria palmata, Sargassum crassifolium, Gelidium spinosum, Gelidiella acerosa, and Gracilaria verrucosa. The macroalgae was collected by purposive sampling in the intertidal zone of Sepanjang Beach. The protein content was analyzed by Biuret method, while the carbohydrate content by the difference method. Results showed that the highest protein and carbohydrate content was found in G. spinosum in central part of Sepanjang Beach at 3.08% and 19.38%, respectively. Based on these results, G. spinosum has the potential to be developed in various processed products with further research.